Grain yield and genotype x environment interaction in bean cultivars with different growth habits - Gustavo Ligarreto–Moreno; Christian Pimentel–Ladino (Plant Production Science, 2021)
Breeding of common beans (Phaseolus vulgaris L.) shows restrictions in the genetic advance because of the effect of the environment. Therefore, the behavior of the yield components of genotypes varies according to the crop’s environment. The genotype x environment interaction can cause genotypes with high yields in one location not to behave in the same way in other localities, which limits the recommendation of cultivars for different environments. The objective of this research was to evaluate agronomic traits in new improved bean cultivars in high tropic environments, as well as to determine which cultivars show phenotypic stability for yield. Multi-environment tests were carried out during 2016 and 2017 in two regions of the department of Cundinamarca, in Colombia. Significant differences were found for the genotype x environment interaction and highly significant differences for the evaluation environments and genotypes. The greatest variation was attributed to genetic effects, followed by environmental effects and the genotype x environment interaction. The first two principal components for grain yield showed 88.86% of the variation of the genotype x environment interaction. Cultivars Serrania and Sutagao, of climbing growth habit, were identified as stable and with high yield potential, so they can be considered as a commercial alternative for bean growers.